2016
DOI: 10.18632/oncotarget.14021
|View full text |Cite
|
Sign up to set email alerts
|

Chemoresistance and targeted therapies in ovarian and endometrial cancers

Abstract: Gynecological cancers are known for being very aggressive at their advanced stages. Indeed, the survival rate of both ovarian and endometrial cancers is very low when diagnosed lately and the success rate of current chemotherapy regimens is not very efficient. One of the main reasons for this low success rate is the acquired chemoresistance of these cancers during their progression. The mechanisms responsible for this acquired chemoresistance are numerous, including efflux pumps, repair mechanisms, survival pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
131
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(134 citation statements)
references
References 301 publications
(298 reference statements)
1
131
0
2
Order By: Relevance
“…EGFR activates the RAS/RAF/MAPK pathway and the PI3K/Akt pathway, which leads to activation of c-Myc and cyclin D1. Members of the ERBB family of receptors serve key roles in chemoresistance (5,22). FGF stimulates SRC proto-oncogene/focal adhesion kinase, SRC/PI3K/Akt, Hedgehog, Notch, transforming growth factor-β and noncanonical WNT signaling cascades and regulates a variety of cellular functions (5,21,22).…”
Section: Growth Factor and Wnt Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…EGFR activates the RAS/RAF/MAPK pathway and the PI3K/Akt pathway, which leads to activation of c-Myc and cyclin D1. Members of the ERBB family of receptors serve key roles in chemoresistance (5,22). FGF stimulates SRC proto-oncogene/focal adhesion kinase, SRC/PI3K/Akt, Hedgehog, Notch, transforming growth factor-β and noncanonical WNT signaling cascades and regulates a variety of cellular functions (5,21,22).…”
Section: Growth Factor and Wnt Pathwaysmentioning
confidence: 99%
“…Mucinous tumors are more frequently detected in early-stage disease with lower tumor grading compared with high-grade serous cancer; however, patients with advanced disease have poor clinical outcome, possibly due to resistance to taxane and platinum-based conventional chemotherapy (4). An evolutionarily conserved signaling cascade system, including growth factor pathways [epidermal growth factor receptor (EGFR), ERBB and fibroblast growth factor receptor (FGFR)] and Wingless (WNT) signaling pathways, regulates a variety of cellular functions, including chemoresistance (5). The crosstalk between EGFR/KRAS proto-oncogene/B-Raf proto-oncogene (BRAF)/mitogen-activated protein kinase (MAPK), phosphatidylinositol-3 kinase (PI3K)/Akt (also known as protein kinase B) and WNT signaling pathways sustains PI3K/glycogen synthase kinase-3β (GSK3β)/β-catenin signal activation, which is associated with chemoresistance in cancer (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…yang berarti tidak ada yang menginduksi apoptosis. 13,14 Penggunaan cisplatin secara tunggal sebagai agen kemoterapi juga sering menimbulkan efek samping seperti mual muntah, hepatotoksisitas, dan neurotoksisitas. Untuk mengurangi efek samping dan resistensi dari cisplatin tersebut, diperlukan kombinasi terapi cisplatin dengan senyawa herbal.…”
Section: Review Articleunclassified
“…Development of drug resistance limits the efficacy of chemotherapy (Brozovic, ). Several signaling pathways in particular Akt are involved in the cellular response to cytotoxic agents (Zhou et al, ; Brasseur et al, ). It has been reported that activation of Akt signaling contributes to cisplatin resistance in ovarian cancer cells induced by chemokine (C‐C motif) ligand 5 (Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%